2020
DOI: 10.2147/ijgm.s274803
|View full text |Cite
|
Sign up to set email alerts
|

<p>Extremely Acute-Onset Cerebral Fat Embolism</p>

Abstract: Cerebral fat embolism (CFE) causes the neurological involvement observed in fat embolism syndrome, which is a post-traumatic complication seen mostly after long bone fractures and usually presents 24-72 h after the injury. An early 80s female who sustained an isolated traumatic fracture of the left distal femur without dislocation was alert on admission but fell into a coma 55 min after the injury. Brain computed tomography showed no abnormalities. Brain magnetic resonance imaging was performed approximately 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Among the reported fulminant FES cases, seven cases [13][14][15][16][17][18], including our case, were identified that developed less than 3 h after injury, with our case being the earliest after injury (Table 2). Most of the fulminant FES cases were severely ill. Another possible mechanism for cerebral fat embolization is that pulmonary fat embolization increases right atrial pressure, causing the leftover patent foramen ovale (PFO) to open, resulting in a right-to-left shunt, which allows fat droplets to flow into the arterial side and cause cerebral infarction [19].…”
Section: Discussionmentioning
confidence: 71%
“…Among the reported fulminant FES cases, seven cases [13][14][15][16][17][18], including our case, were identified that developed less than 3 h after injury, with our case being the earliest after injury (Table 2). Most of the fulminant FES cases were severely ill. Another possible mechanism for cerebral fat embolization is that pulmonary fat embolization increases right atrial pressure, causing the leftover patent foramen ovale (PFO) to open, resulting in a right-to-left shunt, which allows fat droplets to flow into the arterial side and cause cerebral infarction [19].…”
Section: Discussionmentioning
confidence: 71%
“…We performed a filtered search for “within 5 years” and “case report” using the keywords “cerebral fat embolism” and “MRI” in a PubMed search. Of 42 cases of cerebral fat embolism included in 39 papers, 3–41 we analyzed 33 cases 3–17,19–26,28–30,32,34,37,39,40 after excluding the following: (1) cases not available ( n = 2), 27,35 (2) not a case report ( n = 1), 33 (3) not in English ( n = 1), 18 (4) not cerebral fat embolism ( n = 3), 36,38,41 (5) diagnosis obtained by CT instead of MRI ( n = 1), 32 and (6) MRI contraindicated due to a magnetic implant ( n = 1) 31 . Of the 33 cases, SWI of the brain was acquired in 10 cases 4,5,10,12,17,25,34,36,37,41 …”
Section: Discussionmentioning
confidence: 99%
“…In the acute phase (1–4 days), the cranial MRI of CFE patients presents scattered lesions with limited diffusion on T2W, presenting a “starry sky sign.” The subacute phase (5–14 days) presents with cytotoxic cerebral edema in the periventricular and white matter fusion. [ 7 ] SWI and gradient-echo imaging can reflect the dense multiple microhemorrhages (CMBs) in CFE lesions along with the white matter fiber bundles. In our case, multiple pinpoint-like microhemorrhagic foci were seen in the lesion area, spread along the bilateral cortices to the frontal-parietal cortex, called “starry sky sign” on SWI.…”
Section: Discussionmentioning
confidence: 99%